Connexin 43 and Its Hemichannels Mediate Hypoxia–Ischemia-Induced Cell Death in Neonatal Rats. Issue 1 (23rd September 2014) - Wang, Jingwei; Ma, Aihua; Xi, Jiashui; Wang, Yulin; Zhao, Bojun
Wistar rat pups had the left common carotid artery cut, and they were exposed to 8% oxygen with free access to food and water until they were killed at 1, 12, 24, and 48 hours after the hypoxia–ischemia (HI) insult. Connexin 43 (Cx43), hemichannel (HC1), and caspase 3 (Casp3) in cerebral HI tissues were examined by immunohistochemistry and Western blot analyses. Astrocytes cell line, astrocytes transduced with a retroviral empty vector (Psup astrocyte), or a Cx43-specific small hairpin RNA (shRNA) construct (shRNA astrocytes) was treated with oxygen–glucose deprivation (OGD) insult. The viability of astrocytes was assessed by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. The results showed the expression of Cx43, HC1, and Casp3 in rats' brain, and astrocytes and Psup astrocytes increased significantly after 24 hours of HI/OGD insult. Cell viability decreased after 24 hours of the insult. The results suggest that Cx43 and hemichannel are likely to mediate the astrocytic death after HI insult.